2020
DOI: 10.1136/bmjopen-2019-033535
|View full text |Cite
|
Sign up to set email alerts
|

Value of an outpatient transition clinic for young people with inflammatory bowel disease: a mixed-methods evaluation

Abstract: ObjectiveDeveloping and evaluating effective transition interventions for young people (16–25 years) with inflammatory bowel disease (IBD) is a high priority. While transition clinics (TCs) have been recommended, little is known about their operating structures and outcomes. This study aimed to gain insight into the value of a TC compared with direct handover care.DesignControlled mixed-methods evaluation of process outcomes, clinical outcomes and patient-reported outcomes.SettingTwo outpatient IBD clinics in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 41 publications
4
46
0
2
Order By: Relevance
“…As for barriers to a seamless transfer/transition, many previous studies have identified similar factors to our results. [12][13][14][15][16] In discussing transitional care, the specific healthcare environment or medical resources for pediatric health care must be considered. For instance, the practice setting is a major issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for barriers to a seamless transfer/transition, many previous studies have identified similar factors to our results. [12][13][14][15][16] In discussing transitional care, the specific healthcare environment or medical resources for pediatric health care must be considered. For instance, the practice setting is a major issue.…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of the roles of these individuals in multidisciplinary care and maximization of communication between them is of strategic importance 17 . For successful transitional care, one of the ideal models for support of patients with childhood‐onset IBD during the transition period is to implement an outpatient‐based transitional care clinic, run by a multidisciplinary team 15 . Although there is no common definition of a transition clinic and the settings are notably heterogeneous, 18 a multidisciplinary approach and good interaction among the various stakeholders are a potential basis for success for transition 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, however, outpatient transition clinics exist for patients with inflammatory bowel disease, but are lacking for patients with functional gastrointestinal disorders, including constipation. 47…”
Section: Pediatric Chronic Constipation and Transition To Adult Medical Carementioning
confidence: 99%
“…Many previous studies have identified various barriers to a seamless transfer of care, as shown in Table 1 [5, 13, 16, 18, 19, 27]. These cover a range of specialists such as healthcare providers, patients, guardians, and social systems and may be single or multiple.…”
Section: Barriers To Successful Transitionmentioning
confidence: 99%
“…One of the ideal models for support of patients with childhood-onset IBD during the transition period is to implement an outpatient-based transitional care clinic run by a multidisciplinary team [27]. Although there is no common definition of a transition clinic and the settings are notably heterogeneous [17], a multidisciplinary approach and good interaction among the various stakeholders are potential keys of the success of transition [5].…”
Section: Joint Clinic and Alternative Visitmentioning
confidence: 99%